Why God Has Left the Netherlands: Explanations for the Decline of Institutional Christianity in the Netherlands Between 1966 and 2015 - Kregting, Joris (Journal for the scientific study of religion, 2018)
Why has the Netherlands witnessed such a strong process of secularization? This article examines this process very extensively. Based on modernization theory, it follows several social cultural developments in Dutch society over the last 50 years and distinguishes between effects on the individual level as well as on the level of society. We are able to do so because of rich data availability, derived from micro-level longitudinal surveys (God in the Netherlands, Social and Cultural Developments in the Netherlands) enriched with macro-level statistics (Statistics Netherlands). With this integrated approach, we provide explanatory insights into the transition of the Netherlands from a predominant Christian nation to a predominant secular nation. Our analysis clearly shows that macro-level educational expansion has affected this process of secularization in the Netherlands, supplemented with the increase in social security, as a so-called cohort effect. Moreover, the long-term effect of Christian socialization is waning; Dutch people who were raised in a religious way increasingly lapse later in their life.